A mobilidade pendular dos trabalhadores na região metropolitana de Goiânia entre 2000 e 2010 - Nunes, Larissa Camilo (2018)
Displacements are characterized by daily displacements of the population of their homes to the destination, being it for work, study and/or other activities. The commuting implies in a dynamic of daily locomotion, differing from the migrations, because the individuals do not lose their ties from the territories of departure and because they do not have a permanent fixation in another place. Metropolitan spaces are the main destinations for commuting, especially because of the attraction of polarizing urban centers and a for the strong demand of labor in the metropolis, leading workers to cross the city limits. Thus, in this research, we chose the Metropolitan Region of Goiânia (MRG) as a spatial research scope, because of the political, economic and social relevance of the region, and especially because of the evident commuting of the workers who compose it. It was established as a general objective to analyze the commuting of the MRG workers, based on the IBGE data of the years 2000 and 2010, based on the spatial processes that are established, highlighting the centrality, concentration and spatial fragmentation. The methodological steps to carry out the research are based on bibliographical and documentary review of urban space, urban concentration and centrality, urban centers, firms and flows, concept of commuting in the scope of Geography and a configuration of the commuting in metropolitan spaces. Data and information were also collected from secondary sources, mainly the microdata of the Brazilian Institute of Geography and Statistics (IBGE), with the help of the Stata Software, obtaining in this way the starting municipalities of the individuals and which would be the municipalities of destinations chosen by the workers, according to the occupational categories exercised. The MRG is under direct influence of Goiânia. The centrality of the capital is due the fact it concentrates a great number of public and private services and specialized services in the area of education, health, finance, etc. After the stockpiles of land in Goiânia were inflated, the population was pushed to municipalities bordering the capital that did not have adequate urban infrastructure and equipment. The workers settled mainly in Aparecida de Goiânia, Senador Canedo and Trindade. Work is the first factor that influences commuting in metropolitan environments. 190,792 individuals left the municipalities of residence to work in other municipalities, of which, 160,849 arrived in the municipalities of the MRG to take up jobs. The data reaffirm a consolidated economic, social and political center rooted in Goiânia, but we can see the emergence of sub-centers that also attract workers, such as Aparecida de Goiânia, Trindade, Senador Canedo and Goianira. The branches of service provision, administrative activities, construction, domestic services and industry were the occupational categories that received the most pendular workers. Most workers are in positions and activities that pay the lowest salaries and require the minimum of professional and academic qualification, as the case of domestic services and construction. Occupational positions that require higher school and professional qualifications have received fewer commuters such as education, health, arts, culture, sport and recreation. We concluded that a decentralization policy is needed to improve workers' mobility and quality of life, particularly by diversifying the labor market and by expanding the distribution of public services linked to education and training. Health, in line with the needs of each municipality.